Cholinergic innervation of the basal ganglia in humans and other anthropoid primates. Issue 2 (8th July 2016) - Stephenson, Alexa R.; Edler, Melissa K.; Erwin, Joseph M.; Jacobs, Bob; Hopkins, William D.; Hof, Patrick R.; Sherwood, Chet C.; Raghanti, Mary Ann
ABSTRACT: Cholinergic innervation of the basal ganglia is important in learning and memory. Striatal cholinergic neurons integrate cognitive and motivational states with behavior. Given these roles, it is not surprising that deficits in cortical cholinergic innervation have been correlated with loss of cognitive function in Alzheimer's disease and schizophrenia. Such evidence suggests the potential significance of subcortical cholinergic innervation in the evolution of the human brain. To compare humans with other closely related primates, the present study quantified axons and interneurons immunoreactive for choline acetyltransferase (ChAT) in regions of the executive and motor loops of the basal ganglia of humans, great apes, and monkeys. We also compared ChAT‐immunoreactive (ir) interneuron morphological types among species within striatal regions. The results indicate that humans and great apes differ from monkeys in having a preponderance of multipolar ChAT‐ir interneurons in the caudate nucleus and putamen, whereas monkeys have a more heterogeneous representation of multipolar, bipolar, and unipolar interneurons. Cholinergic innervation, as measured by axon and interneuron densities, did not differ across species in the medial caudate nucleus. Differences were detected in the dorsal caudate nucleus, putamen, and globus pallidus but the observed variation did not associate with the phylogenetic structure of the species in the sample. However, combining the present results with previously published data for dopamine revealed a unique pattern of innervation for humans, with higher amounts of dopamine compared with acetylcholine in the striatum. Taken together, these findings indicate a potential evolutionary shift in basal ganglia neurotransmission in humans that may favor increased synaptic plasticity. J. Comp. Neurol. 525:319–332, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Primates exhibit species‐specific cholinergic innervation within the basal ganglia. Monkeys possess mostly bipolar striatal cholinergic neurons, whereas humans and apes have a preponderance of multipolar subtypes. Humans are unique in having higher striatal dopaminergic innervation compared with cholinergic, indicating a potential shift in basal ganglia neurotransmission that may favor increased synaptic plasticity.